Post spike syndrome (PSS): Simple solution leading to resolving results, five cases report - Roberto S. Zeballos; Mariely Fernanda da Silva Helbingen; Paulo Macio Porto Melo; Francisco Eduardo Cardoso Alves; Caio Roberto Salvino; Ewerton Paes Seródio; Edimilson Ramos Migowski de Carvalho (IDCases, 2025)
Post-Spike Syndrome (PSS) is an emerging condition associated with the Spike protein, originating from both SARS-CoV-2 infection and mRNA-based therapies. This case series explores the significant clinical impact of PSS, characterized By gut dysbiosis, systemic inflammation, and immune activation, leading to multisystem manifestations such as fatigue, brain fog, neuropathies, and reactivation of pre-existing diseases. A simple therapeutic approach was applied to five patients, resulting in notable symptom improvement. Methods: This case series includes five patients diagnosed with interstitial granulomatous dermatitis, polymyalgia rheumatica, peripheral polyneuropathy, drug-refractory epilepsy, and trigeminal neuralgia. A common pathophysiological mechanism—vasculitis triggered by both SARS-CoV-2 and mRNA-based therapies—was hypothesised. The patients exhibited a satisfactory response to the proposed therapeutic strategy. This is an observational and descriptive study, with data collected retrospectively from medical records at a private clinic in São Paulo, Brazil. Conclusion: It is crucial to raise awareness within the medical community About SPIKEOPATHY, particularly in cases of classic pathologies that do not respond to conventional treatments. We believe PSS is currently underestimated. A broad intervention including a focus on restoring the microbiome, in particular Bifidobacterium associated with ivermectin and nattokinase was used as a therapeutic strategy. In other studies, Bifidobacterium has already been shown to significantly reduce harmful bactéria in post-COVID patients. Further studies are needed to confirm these findings and expand our understanding of PSS management.